Negative electrode material, negative electrode plate and secondary battery

By filling amorphous carbon into natural graphite and limiting the particle hardness and elastic modulus, the problems of low first coulombic efficiency and insufficient cycle stability of the negative electrode material are solved, efficient lithium ion diffusion and structural stability are achieved, and the overall performance of the secondary battery is improved.

CN120613399APending Publication Date: 2025-09-09BTR NEW MATERIAL GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510776785.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

Existing negative electrode materials have problems such as low first coulombic efficiency and insufficient cycle stability during the charge and discharge process, especially the SEI film instability and uneven lithium ion embedding caused by the anisotropy and internal defects of natural graphite.

Method used

The negative electrode material is made of natural graphite filled with amorphous carbon. By limiting the particle hardness to 0.28GPa~0.4GPa, the elastic modulus to 7.0GPa~8.0GPa and the tablet orientation OI value to 4

Benefits of technology

The initial coulombic efficiency was significantly improved to over 94%, and the capacity retention rate was ≥92.5% after 400 cycles, thus enhancing the electrochemical performance and cycle stability of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120613399A_ABST
    Figure CN120613399A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material, a negative electrode plate and a secondary battery, and relates to the technical field of secondary batteries. The negative electrode material comprises natural graphite and amorphous carbon filled in pores of the natural graphite; the particle hardness of the negative electrode material is 0.28 GPa to 0.4 GPa, and the elastic modulus of the negative electrode material is 7.0 GPa to 8.0 GPa; and when the compaction density of the tablet of the negative electrode material is 1.5-2.0 g / cm < 3 >, the orientation OI value of the tablet of the negative electrode material is y, and y is more than 4 and less than or equal to 11. When the negative electrode material is applied to the secondary battery, the first coulombic efficiency and the cycling stability can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with the application date of December 16, 2024, application number 202411850897.7, and invention name "A negative electrode material, negative electrode sheet and secondary battery". Technical Field

[0002] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material, a negative electrode sheet and a secondary battery. Background Art

[0003] Lithium-ion batteries are widely used in 3C (3C) applications, power devices, and energy storage devices due to their advantages such as low self-discharge, high charge and discharge efficiency, no memory effect, and long cycle life. Negative electrode materials are a crucial component of lithium-ion batteries, and their performance directly impacts their electrochemical performance. Natural graphite negative electrode materials have attracted widespread attention due to their high specific capacity, low charge and discharge plateau, and low cost. However, natural graphite has high anisotropy and internal defects, making it prone to solvent co-intercalation during lithium-ion intercalation, resulting in reduced SEI film stability, consumption of additional lithium ions, and reduced initial coulombic efficiency. Furthermore, these high defects can cause graphite to undergo uneven volume expansion. During the long-term cycling of lithium-ion batteries, the continuous expansion and contraction of the graphite structure can lead to further expansion of defective areas, and even to the shedding of graphite sheets and the formation of cracks, causing capacity decay over long cycles. Summary of the Invention

[0004] The main purpose of the present invention is to provide a negative electrode material, a negative electrode sheet and a secondary battery to solve the problems of low initial coulombic efficiency and insufficient cycle stability of negative electrode materials in the prior art during the charge and discharge process.

[0005] To achieve the above object, according to one aspect of the present invention, a negative electrode material is provided, which comprises natural graphite and amorphous carbon filled in the pores of the natural graphite; the particle hardness of the negative electrode material is 0.28GPa to 0.4GPa, and the elastic modulus is 7.0GPa to 8.0GPa; when the compaction density of the negative electrode material is 1.5 to 2.0g / cm 3 , the OI value of the negative electrode material's tablet orientation is y, 4<y≤11.

[0006] Furthermore, the particle hardness of the negative electrode material is 0.287 GPa, 0.288 GPa, 0.295 GPa, 0.308 GPa, 0.335 GPa, 0.356 GPa, 0.393 GPa or any value within the range consisting of any two of the above values.

[0007] Furthermore, the elastic modulus of the negative electrode material is 7.08 GPa, 7.15 GPa, 7.26 GPa, 7.45 GPa, 7.78 GPa, 7.9 GPa, 7.96 GPa, or any value within the range consisting of any two of the foregoing values.

[0008] Furthermore, when the compaction density of the negative electrode material is 1.5 to 2.0 g / cm 3 When the negative electrode material is oriented, the OI value of the pressed sheet is 4.05, 4.48, 4.68, 5.4, 5.53, 5.92, 6.1, 6.31, 6.58, 6.62, 7.38, 7.94, 8.11, 8.46, 8.51, 8.67, 9.73 or any value within the range of any two of the above values.

[0009] Furthermore, the tableting orientation OI value of the negative electrode material at different tableting densities is y, satisfying: y1≤y≤y2;

[0010] Wherein, y1=5.46x-3.78, y2=8.9x-7.76, 1.5≤x≤2.0, and x is the value corresponding to the tablet compaction density of the negative electrode material.

[0011] Furthermore, when the compaction density of the negative electrode material is 1.5 to 2.0 g / cm 3 , the OI value of the negative electrode material's tablet orientation is 5 to 10.

[0012] Furthermore, the negative electrode material satisfies at least one of the following characteristics:

[0013] (1) The sphericity Sh (90%) of the negative electrode material is 0.90 to 0.95;

[0014] (2) The D50 volume average particle size of the negative electrode material is 8 to 18 μm;

[0015] (3) The average particle size of the negative electrode material is 10 to 20 μm.

[0016] Furthermore, the shape factor of the negative electrode material The sphericity Sh (90%) of the negative electrode material satisfies: ∣, and Δ≤0.08; where, D1 is the D50 volume average particle size of the negative electrode material, in μm; D2 is the equal volume average particle size of the negative electrode material, in μm.

[0017] Furthermore, the specific surface area of ​​the negative electrode material is 2 to 5 m 2 / g.

[0018] Furthermore, the tap density of the negative electrode material is 0.9 to 1.3 g / cm 3 .

[0019] Furthermore, the powder compaction density of the negative electrode material is 1.7 to 2.0 g / cm 3 .

[0020] A second aspect of the present invention provides a negative electrode sheet, which includes the negative electrode material provided by the first aspect.

[0021] A third aspect of the present invention provides a secondary battery, comprising the negative electrode sheet provided in the second aspect.

[0022] The technical solution of the present invention improves the densification of the negative electrode material, reduces the anisotropy of the negative electrode material, and makes the diffusion of lithium ions in different directions more uniform, which helps improve the electrochemical performance of the negative electrode material. At the same time, by limiting the particle hardness of the negative electrode material to 0.28GPa to 0.4GPa, the elastic modulus to 7.0GPa to 8.0GPa, and the tableting orientation OI value to y, 4<y≤11, the structural stability of the negative electrode material can be enhanced, and the volume expansion can be effectively controlled, ensuring that the negative electrode material can maintain structural stability during the charge and discharge process. At the same time, it ensures that the negative electrode material has unobstructed lithium ion channels on its surface and inside, reducing the problems of sheet shedding and crack formation, thereby improving cycle stability. When used in secondary batteries, this negative electrode material can achieve an initial coulombic efficiency of ≥94% and a capacity retention rate of ≥92.5% after 400 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic structural diagram of a secondary battery during charging provided by one embodiment of the present invention;

[0024] Figure 2 A schematic structural diagram of a secondary battery provided in one embodiment of the present invention during discharge;

[0025] Figure 3 This is a SEM image of the negative electrode material in Example 1 of the present invention;

[0026] Figure 4 1 is a coordinate diagram of the OI value of the tableting orientation of the negative electrode materials at different compaction densities in the embodiments of the present invention and the comparative examples.

[0027] Description of reference numerals:

[0028] 100 - electrode assembly; 101 - positive electrode sheet; 102 - negative electrode sheet; 103 - separator. DETAILED DESCRIPTION

[0029] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.

[0030] As described in the background of the present invention, the negative electrode materials in the prior art have the problems of low initial coulombic efficiency and insufficient cycle stability during the charge and discharge process. In order to solve the above problems, in a typical embodiment of the present invention, a negative electrode material is provided, which includes natural graphite and amorphous carbon filled in the pores of natural graphite; the particle hardness of the negative electrode material is 0.28GPa to 0.4GPa, and the elastic modulus is 7.0GPa to 8.0GPa; when the tablet compaction density of the negative electrode material is 1.5 to 2.0g / cm 3 , the OI value of the negative electrode material's tablet orientation is y, 4<y≤11.

[0031] The negative electrode material includes natural graphite and amorphous carbon filled in the pores of natural graphite, which improves the density of the negative electrode material. At the same time, since amorphous carbon is highly disordered, the filling of amorphous carbon can reduce the anisotropy of the negative electrode material, making the diffusion of lithium ions in different directions more uniform, which helps to improve the electrochemical performance of the negative electrode material.

[0032] The particle hardness and elastic modulus of negative electrode materials are crucial to the electrochemical performance and cycling stability of secondary batteries. They also reflect the degree of internal densification and amorphous carbon filling within the particles. The particle hardness (HIT) of the negative electrode material directly reflects the ability of the graphite particles to resist elastic and plastic deformation under external forces. The elastic modulus (EIT) of the negative electrode material reflects its ability to resist external forces during the elastic deformation stage, i.e., the stress required to produce a unit strain in the material under load.

[0033] The particle hardness of the negative electrode material affects its volume expansion and contraction. By limiting the particle hardness of the negative electrode material to 0.28GPa to 0.4GPa, the graphite particles have sufficient mechanical strength to withstand the volume expansion and contraction generated during the insertion and extraction of lithium ions. This means that they can better resist the mechanical stress in this process, helping to reduce particle fragmentation and shedding during cycling, thereby improving cycle stability. Secondly, it helps to limit the expansion of the pores inside the particles, reducing the probability of electrolyte solvent molecules and lithium ions being co-intercalated between the graphite layers, thereby reducing excessive consumption of the SEI film and improving the initial coulombic efficiency. In addition, during the charge and discharge cycles of secondary batteries, graphite particles undergo repeated volume changes. When the particle hardness is 0.28GPa to 0.4GPa, it helps to maintain the structural integrity of the negative electrode material, reduce capacity decay caused by mechanical wear and structural damage, and extend the service life of the secondary battery. Specifically but not limitatively, the particle hardness of the negative electrode material is 0.287 GPa, 0.288 GPa, 0.295 GPa, 0.308 GPa, 0.335 GPa, 0.356 GPa, 0.393 GPa or any value within the range of any two of the above values.

[0034] The elastic modulus of the negative electrode material is related to its stress-strain properties. By limiting the elastic modulus of the negative electrode material to 7.0GPa to 8.0GPa, it is shown that the elastic deformation of the negative electrode material during the lithium ion insertion and deinsertion process can be well controlled, effectively alleviating the volume change of the negative electrode material during the cycle, enabling it to better adapt to volume changes, reducing cracks and particle shedding caused by stress concentration, and helping to improve cycle stability. Secondly, it helps stabilize the SEI film during the charge and discharge cycle, reducing film rupture caused by material expansion, thereby improving the first coulombic efficiency and cycle performance. In addition, the elastic modulus is related to the diffusion dynamics of lithium ions in the negative electrode material. A suitable elastic modulus means lower stress inside the material and a smoother lithium ion diffusion path, which helps to increase the lithium ion transmission rate, thereby improving the electrochemical performance of the secondary battery, such as charge and discharge rate and capacity. Specifically but not limitatively, the elastic modulus of the negative electrode material is 7.08 GPa, 7.15 GPa, 7.26 GPa, 7.45 GPa, 7.78 GPa, 7.9 GPa, 7.96 GPa, or any value within the range of any two of the foregoing values.

[0035] The negative electrode material has diffraction peaks at (004) and (110) planes in the X-ray diffraction pattern, and the OI value of the pressed tablet orientation of the negative electrode material is the ratio of the diffraction peak area at the (004) plane to the diffraction peak area at the (110) plane. In some embodiments, when the pressed tablet density of the negative electrode material is 1.5 to 2.0 g / cm 3, the OI value of the tablet orientation of the negative electrode material is y, 4<y≤11. The OI value of the tablet orientation is a parameter that describes the degree of order of the graphite sheet arrangement in the negative electrode material. By limiting the OI value of the tablet orientation to y, 4<y≤11, it helps to improve the kinetic properties of the material. Since amorphous carbon is highly disordered, the filling of amorphous carbon can reduce the OI value of the tablet orientation. This disorder helps to prevent the solvent in the electrolyte from being co-embedded in the graphite layer, thereby improving the interfacial transport kinetics of lithium ions. The present invention helps to improve the first coulombic efficiency and cycle stability of the negative electrode material by limiting the OI value of the tablet orientation within the above range. Specifically, but not restrictively, when the tablet compaction density of the negative electrode material is 1.5~2.0g / cm 3 The OI value of the negative electrode material in the sheet orientation is 4.05, 4.48, 4.68, 5.4, 5.53, 5.92, 6.1, 6.31, 6.58, 6.62, 7.38, 7.94, 8.11, 8.46, 8.51, 8.67, 9.73 or any value within the range of any two of the above values.

[0036] The present invention limits the particle hardness of the negative electrode material to 0.28GPa~0.4GPa, the elastic modulus to 7.0GPa~8.0GPa, and the tablet orientation OI value to y, 4<y≤11, which not only reflects the high degree of internal densification of the particles and the high degree of amorphous carbon filling, but also achieves a balance between structural stability and lithium ion transport kinetics, taking into account the improvement of the first coulomb efficiency and cycle stability. Specifically, on the one hand, the structural integrity of the negative electrode material during the cycle is guaranteed, thereby improving the cycle stability; on the other hand, the diffusion path of lithium ions in the negative electrode material is optimized, which is conducive to improving electrochemical performance, such as the first coulomb efficiency. This synergistic effect helps the negative electrode material maintain moderate elastic deformation during the lithium ion insertion and deinsertion process, avoid excessive plastic deformation, maintain a more stable SEI film and better electrochemical performance, thereby taking into account the improvement of the first coulomb efficiency and cycle stability.

[0037] The particle hardness and elastic modulus of the negative electrode material can be determined by an indentation hardness test, for example, a nanoindenter can be used for measurement. During the test, a hard indenter is pressed into the particle surface with a certain force and then unloaded. The hardness value of the negative electrode material is calculated by measuring the depth and width of the indentation, as well as the magnitude of the applied force. The elastic modulus is calculated by measuring the unloading process of the indentation on the material surface. At least 10 particles are tested for each sample, and the average values ​​of the hardness value and elastic modulus are taken after the test, that is, the particle hardness and elastic modulus of the negative electrode material.

[0038] According to the research of the present invention, the above-mentioned negative electrode material is applied to the secondary battery, which can significantly improve the first coulombic efficiency and cycle stability. This is because, on the one hand, due to the amorphous carbon in the natural graphite pores in the negative electrode material of the present application, the densification degree of the negative electrode material is improved, the anisotropy of the negative electrode material can be reduced, and the diffusion of lithium ions in different directions is more uniform, which helps to improve the electrochemical performance of the negative electrode material; on the other hand, by limiting the particle hardness of the negative electrode material to 0.28GPa~0.4GPa and the elastic modulus to 7.0GPa~8.0GPa, the tablet orientation OI value is y, 4<y≤11, which not only shows that the internal density of the particles is high and the amorphous carbon filling degree is high, but also makes the negative electrode material have appropriate mechanical strength and deformation ability, which can resist the volume change during the charge and discharge process and optimize the transmission dynamics of lithium ions, thereby improving the stability of the SEI film and the overall performance of the secondary battery. Applying this negative electrode material to secondary batteries can achieve an initial coulombic efficiency of ≥94% and a capacity retention rate of ≥92.5% after 400 cycles, which helps to obtain a more efficient, stable and long-life secondary battery.

[0039] In some preferred embodiments, the negative electrode material's tablet orientation OI value y at different tablet compaction densities satisfies the following: y1≤y≤y2; where y1 = 5.46x-3.78, y2 = 8.9x-7.76, 1.5≤x≤2.0, and x is the value corresponding to the negative electrode material's compaction density; y2 and y1 represent the upper and lower limits of the tablet orientation OI value at different compaction densities, respectively. By limiting the negative electrode material's tablet orientation OI value and tablet compaction density to meet these requirements, the negative electrode material can be highly isotropic, minimizing the polarization effect during charging, limiting the volume effect, and reducing the formation of new SEI. This not only further improves the initial coulombic efficiency and cycle stability, but also maximizes capacity, thereby simultaneously improving the initial coulombic efficiency, capacity, and cycle stability of the negative electrode material.

[0040] Specifically, when the compaction density of the negative electrode material is 1.5 g / cm 3 , that is, when x is 1.5, y1=4.41, y2=5.59, at this time, 4.41≤y≤5.59, the tablet orientation OI value is 4.41~5.59; when the tablet compaction density of the negative electrode material is 2g / cm 3 , that is, when x is 2, y1=7.14, y2=10.04, at this time, 7.14≤y≤10.04, the tablet orientation OI value is 7.14-10.04, and so on. In the specific implementation process of the present invention, the tablet compaction density of the negative electrode material actually refers to the compaction density of the tablet formed by the negative electrode material under different pressures.

[0041] In some preferred embodiments, the tablet orientation OI value y of the negative electrode material at different tablet compaction densities satisfies: y1≤y≤y2; wherein, y1=5.46x-3.78, y2=8.88x-8.

[0042] In some preferred embodiments, the negative electrode material has a pressed sheet orientation OI value of 5 to 10, preferably 5 to 9, which can further improve the first coulombic efficiency and cycle stability of the negative electrode material.

[0043] The geometry of the negative electrode material particles has a certain influence on the electrochemical performance and cycle stability. The geometry of the particles affects the contact area with the electrolyte and the mechanical stability during the charge and discharge process, thereby affecting the charge and discharge performance and cycle stability of the secondary battery. In some embodiments, the shape factor of the negative electrode material is And the sphericity Sh (90%) of the negative electrode material satisfies: And Δ≤0.08; where, D1 is the D50 particle size of the negative electrode material, in μm; D2 is the average particle size of the negative electrode material in μm. It can be understood that Δ is The absolute value of the difference between Sh (90%) and Sh (90%). The particle sphericity Sh (90%) satisfies the above relationship, ensuring excellent inter-particle contact and good mechanical stability, resisting volume expansion and contraction, thereby improving the charge-discharge performance and cycling stability of the secondary battery. In some preferred embodiments, Δ ≤ 0.06, further improving charge-discharge performance and cycling stability.

[0044] Sphericity refers to the degree to which particles are close to spheres. The sphericity Sh (90%) of the negative electrode material refers to the ratio of the maximum diameter to the minimum diameter of the particles among 90% of the particles. The closer this ratio is to 1, the closer the particles are to a perfect sphere. In some embodiments, the sphericity Sh (90%) of the negative electrode material is 0.90 to 0.95, which means that most of the graphite particles have a high sphericity. In addition to helping to further improve the first coulomb efficiency and cycle stability of the secondary battery, this geometric form helps to form a denser structure during the compaction process, which helps to improve the energy density of the secondary battery. In addition, spherical graphite particles are isotropic and can form a more uniform lithium ion transmission path and a more stable conductive network. Compared with irregularly shaped particles, spherical particles are more orderly arranged in the electrode, which can reduce the electron and lithium ion transmission resistance inside the secondary battery and improve the charge and discharge rate and capacity of the secondary battery.

[0045] The D50 volume-average particle size is the particle size corresponding to the cumulative volume distribution percentage in the sample reaching 50%, reflecting the average particle size of the negative electrode material. In some embodiments, the D50 volume-average particle size of the negative electrode material is 8-18 μm. The isovolume-average particle size refers to the average particle size of a sphere with the same average volume as the particles. In some embodiments, the isovolume-average particle size of the negative electrode material is 10-20 μm. By limiting the D50 volume-average particle size and isovolume-average particle size of the negative electrode material to an appropriate range, in addition to further improving the initial coulombic efficiency and cycle stability of the secondary battery, the diffusion path of lithium ions can be shortened, reducing the transport resistance of lithium ions during the insertion and deinsertion processes, thereby improving the charge and discharge efficiency. In addition, the internal porosity of the electrode can be reduced, thereby increasing the energy density of the secondary battery. In some preferred embodiments, the D50 volume-average particle size of the negative electrode material is 10-18 μm, and the isovolume-average particle size is 11-18 μm.

[0046] Specific surface area (SSA) refers to the total surface area per unit mass of a material. In some embodiments, the specific surface area of ​​the negative electrode material is 2 to 5 m 2 By limiting the specific surface area of ​​the negative electrode material to an appropriate range, in addition to further improving the initial coulombic efficiency and cycle performance, it can also provide an appropriate diffusion path, which not only avoids the performance degradation caused by the electrolyte penetrating into the internal pores of the material, but also facilitates the rapid and uniform diffusion of lithium ions during the charge and discharge process, thereby improving the rate performance and cycle stability of the secondary battery. In addition, it can reduce the contact between the electrolyte and the surface of the graphite material, reducing the possibility of side reactions such as electrolyte decomposition and co-intercalation of solvent molecules.

[0047] Tap density (Tap) refers to the compactness of a material under physical vibration. In some embodiments, the tap density of the negative electrode material is 0.9 to 1.3 g / cm 3 . By limiting the tap density of the negative electrode material to a moderate range, it helps to improve the compaction density of the material during the electrode manufacturing process, reduce the internal pores of the electrode, improve the utilization rate of the negative electrode material and the energy density of the secondary battery, and at the same time reduce the contact area between the electrolyte and the graphite particles, thereby reducing the formation of the SEI film, reducing the irreversible capacity during the first charge and discharge, and improving the first coulomb efficiency; it also helps to reduce the volume expansion during the cycle, reduce the mechanical stress between the particles, and prevent the formation of cracks, thereby improving the cycle stability. In addition, it helps to maintain the integrity of the electrode structure, prevent the active material from falling off the current collector, and further improve the cycle performance. In some preferred embodiments, the tap density of the negative electrode material is 1 to 1.3 g / cm 3 .

[0048] The powder compaction density refers to the density of the negative electrode material powder under a certain pressure (e.g., 2T), which is usually determined by compacting the material under a certain pressure and then measuring the volume and mass of the material after compaction. The powder compaction density is directly related to the energy density, first coulomb efficiency, and cycle stability of the secondary battery. In some embodiments, the powder compaction density of the negative electrode material is 1.7 to 2.0 g / cm 3 By limiting the powder compaction density to an appropriate range, the graphite particles can be brought into closer contact, helping to form a more uniform and stable SEI film, further improving the initial coulombic efficiency. This also reduces the relative movement between particles and reduces the mechanical stress on the graphite particles during the charge and discharge cycle, further improving cycle stability. Furthermore, this allows for a more uniform distribution of the negative electrode material, helping to increase energy density.

[0049] The negative electrode material of the present invention can be used as a negative electrode material in secondary batteries, effectively improving the initial coulombic efficiency and cycling stability of the secondary battery. For example, in some embodiments, the negative electrode material has an initial coulombic efficiency of 94% or higher, a capacity retention rate of 92.5% or higher after 400 cycles, and a capacity of 360 mAh / g or higher.

[0050] The present invention does not limit the specific preparation process of the negative electrode material, as long as the above parameters are met. In some embodiments, the preparation method of the negative electrode material includes the following steps:

[0051] S1, oxidizing the graphite raw material to obtain graphite oxide;

[0052] S2, sequentially mixing and coating graphite oxide and asphalt, and subjecting them to a first heat treatment to obtain a composite;

[0053] S3, densifying the complex to obtain an intermediate product;

[0054] S4, subjecting the intermediate product to a second heat treatment to obtain a negative electrode material.

[0055] Specifically, in S1, the graphite raw material is oxidized to effectively improve the surface activity of the graphite raw material, which not only promotes the uniformity in the subsequent coating process, but also helps to improve the compatibility and stability of the material with the electrolyte, so as to achieve mechanical properties that match the insertion / deinsertion of lithium ions.

[0056] The specific temperature, gas content, and time of the oxidation treatment can be adjusted according to actual conditions. For example, in some embodiments, the graphite raw material can be natural graphite, which can be, for example, spherical graphite. The spherical graphite has a D50 volume average particle size of 1 to 20 μm. This particle size range ensures the uniformity and stability of the material during subsequent processing. The oxidation treatment can be carried out at an oxygen volume content of 1% to 10%, at a temperature of 400 to 600°C, and for 2 to 3 hours.

[0057] In S2, graphite oxide is mixed and coated with asphalt. It can be understood that the graphite oxide and asphalt are mixed at room temperature. During the mixing and coating process, the asphalt and graphite oxide are evenly mixed to form a mixture. The mixture is then subjected to a first heat treatment to allow the molten asphalt to fill the pores within the graphite, thereby forming a composite. The mixing, coating, and first heat treatment help improve the material's density, firmness, and hardness.

[0058] The specific mixing ratio of graphite oxide and asphalt can be adjusted according to the material properties and requirements. For example, in some embodiments, the mass ratio of graphite raw material to asphalt is 100: (1 to 30); the asphalt is selected from at least one of petroleum asphalt, coal asphalt, and mesophase asphalt, and the D50 volume average particle size of the asphalt is 2 to 3 μm; the asphalt softening point is 100 to 300°C, and the mixing coating time is 10 to 60 minutes; the first heat treatment can be carried out in a first inert atmosphere at a temperature higher than the asphalt softening point; the first inert atmosphere is to prevent oxidation of the material during the heat treatment process, and any inert gas can achieve this purpose, for example, it can include at least one of nitrogen, helium, and argon; the temperature of the first heat treatment is 200 to 600°C, and the time is 3 to 4 hours.

[0059] In S3, the densification process includes profiling and isostatic pressing. Specifically, the composite is first profiling with a hydraulic press to obtain a profiling product. The profiling product is then isostatically pressed to obtain an isostatically pressed product. Finally, the isostatically pressed product is crushed to obtain an intermediate product. The densification process effectively reduces the internal pores of the graphite, increases the material's density, enhances its structural compactness, and improves pore filling, thereby ensuring that the material's particle hardness and elastic modulus meet the aforementioned requirements.

[0060] The specific pressure, time, and number of cycles of the profiling treatment can be adjusted according to the actual equipment capabilities and material requirements. For example, in some embodiments, the profiling conditions are: the pressure of the hydraulic press is 10 to 40 MPa, the holding time is 0 to 2 minutes, and the pressure is released for 0.5 minutes before slowly reciprocating 2 to 4 times. The short holding time can ensure that the material quickly forms a dense structure under high pressure, while avoiding equipment wear and reduced production efficiency caused by long-term holding time. It is suitable for continuous production processes and can improve production efficiency and equipment utilization. Isostatic pressing can further improve the density and structural stability of the material, and the specific pressure and time can be optimized according to the performance requirements of the material and the equipment capabilities. For example, in the isostatic pressing treatment, the filling effect of asphalt inside the graphite can be controlled by regulating the pressure. For example, the isostatic pressing treatment can adopt cold isostatic pressing or warm isostatic pressing. The pressure of the isostatic pressing treatment is 60 to 120 MPa, and the holding time is 1 to 60 minutes.

[0061] In S4, the intermediate product undergoes a second heat treatment under a second inert atmosphere to ensure the degree of graphitization of the material. After the second heat treatment, the negative electrode material is obtained after being dispersed, demagnetized, and screened. The second heat treatment converts the pitch into amorphous carbon, ensuring stable carbonization of the material at high temperatures and increasing its degree of graphitization. Appropriate heat treatment temperature and time can affect the crystallinity and microstructure of the graphite, thereby ensuring that its hardness and elastic modulus meet the aforementioned requirements.

[0062] The specific temperature and time of the second heat treatment can be adjusted according to the conditions of the heat treatment device and the performance target of the material. For example, in some embodiments, the temperature of the second heat treatment is greater than the temperature of the first heat treatment, for example, the temperature of the second heat treatment is 900-1600°C and the time is 10-24 hours. The second inert atmosphere is to prevent oxidation of the material during the heat treatment process. Any inert gas can achieve this purpose, for example, it can include at least one of nitrogen, helium, and argon.

[0063] A second aspect of the present invention provides a negative electrode sheet, which includes the negative electrode material provided by the first aspect.

[0064] The negative electrode sheet of the present invention includes a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode material active layer includes the negative electrode material provided in the first aspect. The negative electrode current collector can be at least one of copper foil, nickel foil, stainless steel foil, titanium foil, or a carbon-based current collector, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining the aforementioned conductive foil and a polymer substrate. Because it includes a high-performance negative electrode material, the negative electrode sheet is used in a secondary battery, which helps improve the initial coulombic efficiency and cycle stability of the secondary battery.

[0065] The negative electrode material active layer also includes a binder to bind the negative electrode active material particles to facilitate film formation and improve the bonding strength between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon.

[0066] The negative electrode material active layer may further comprise a conductive material, including but not limited to carbon-based materials, metal-based materials, conductive polymers, or any combination thereof. In some embodiments, carbon-based materials may include, but are not limited to, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, or any combination thereof. In some embodiments, metal-based materials may include, but are not limited to, metal powders or metal fibers, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0067] To prepare the negative electrode sheet, the negative electrode material, conductive agent, and binder are dispersed in an appropriate amount of solvent and thoroughly stirred to form a uniform negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector, dried, rolled, and slit to obtain the negative electrode sheet. In one embodiment, the negative electrode active layer comprises, by weight, 70% to 99% negative electrode material, 0.5% to 15% conductive agent, and 0.5% to 15% binder.

[0068] The conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate. A third aspect of the present invention provides a secondary battery comprising the negative electrode sheet provided in the second aspect.

[0069] Due to the inclusion of the above-mentioned negative electrode sheet with excellent performance, the secondary battery has excellent first coulombic efficiency and cycle stability.

[0070] Specifically, the secondary battery includes a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.

[0071] The outer shell can be a packaging bag obtained by packaging film (such as aluminum-plastic film), for example, a soft pack battery. In other embodiments, it can also be a steel shell battery, an aluminum shell battery, etc.

[0072] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is provided between the positive electrode sheet 101 and the negative electrode sheet 102. Figure 1 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 2 Active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the electrolyte through the isolation membrane 103, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101. The reverse movement of the electrons forms an electric current that can be used by electrical appliances.

[0073] In some embodiments, the electrode assembly 100 may be a laminated structure, formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may be a wound structure, formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.

[0074] The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector can be made of aluminum foil or nickel foil, etc., or it can be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and the polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and deintercalate lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).

[0075] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate film formation and improve the bonding strength between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include, but is not limited to, at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon.

[0076] The positive electrode material active layer may further comprise a conductive material, including but not limited to carbon-based materials, metal-based materials, conductive polymers, or any combination thereof. In some embodiments, the carbon-based material may include, but is not limited to, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include, but is not limited to, metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0077] The separator 103 comprises a porous membrane layer, and its material includes, but is not limited to, at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide, or aramid. For example, the separator 103 may be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane.

[0078] The electrolyte conducts ions between the positive electrode 101 and the negative electrode 102. The electrolyte can be in one or more of a gel, solid, and liquid state. In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution conducts active ions between the positive electrode 101 and the negative electrode 102. In some embodiments, the electrolyte solution includes a lithium salt and an organic solvent. The lithium salt may be selected from, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(SO2CF3)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium bisoxalatoborate (LiBOB), and lithium difluorophosphate (LiPO2F2). For example, LiPF6 is selected as the lithium salt because it can provide high ionic conductivity and improve cycle characteristics. The organic solvent may be a carbonate compound, a carboxylate compound, an ether compound, a nitrile compound, other organic solvents, or a combination thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.

[0079] When preparing secondary batteries, the positive electrode sheets, separators and negative electrode sheets are wound or stacked to obtain battery cells, which are then encapsulated in pre-stamped aluminum-plastic films. After the encapsulated batteries are dried to remove moisture, the electrolyte is injected into the dried batteries. After the batteries are aged, formed and sealed for the second time, the preparation of the secondary batteries is completed.

[0080] The present application is further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application.

[0081] Example 1

[0082] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0083] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) was kept at a temperature of 500° C. and an oxygen volume content of 5% for 3 hours, and then cooled to room temperature to obtain graphite oxide;

[0084] S2, graphite oxide and 2.2 kg of petroleum asphalt (softening point of 250 ° C) were added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture was heat-treated at 400 ° C for 4 hours in a nitrogen atmosphere and cooled to room temperature to obtain a composite;

[0085] S3, densifying the composite by pressing it in a hydraulic press at a pressure of 30 MPa, holding the pressure for 0.5 min, and reciprocating twice, and then performing isostatic pressing densification at a maximum pressure of 70 MPa, holding the pressure for 3 min, and then pulverizing to obtain an intermediate product;

[0086] S4, carbonizing the intermediate product at 1250° C. for 16 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.

[0087] Example 2

[0088] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0089] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) was kept at a temperature of 450° C. and an oxygen content of 6% for 3 hours, and then cooled to room temperature to obtain graphite oxide;

[0090] S2, graphite oxide and 2.2 kg of coal tar pitch (softening point 180°C) were added to a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat-treated at 350°C for 4 h in a nitrogen atmosphere and cooled to room temperature to obtain a composite.

[0091] S3, densifying the composite by pressing it in a hydraulic press at a pressure of 20 MPa, holding the pressure for 0.5 min, and reciprocating twice, and then performing isostatic pressing densification treatment at a maximum isostatic pressing pressure of 70 MPa, holding the pressure for 3 min, and then pulverizing to obtain an intermediate product;

[0092] S4, carbonizing the intermediate product at 1250° C. for 14 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.

[0093] Example 3

[0094] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0095] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) was kept at a temperature of 500°C and an oxygen content of 6% for 3 hours, and then cooled to room temperature to obtain graphite oxide;

[0096] S2, graphite oxide and 1.6 kg of coal tar pitch (softening point 180°C) were added to a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat-treated at 350°C for 3 h under a nitrogen atmosphere. After cooling to room temperature, a composite was obtained;

[0097] S3, densifying the composite by pressing it in a hydraulic press at a pressure of 20 MPa, holding the pressure for 0.5 min, and reciprocating twice, and then performing isostatic pressing densification treatment at a maximum isostatic pressing pressure of 60 MPa, holding the pressure for 3 min, and then pulverizing to obtain an intermediate product;

[0098] S4, carbonizing the intermediate product at 1250° C. for 12 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.

[0099] Example 4

[0100] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0101] S1, 20 kg of graphite raw material (D50 volume average particle size of 14.5 μm) was kept at a temperature of 500° C. and an oxygen content of 5% for 3 h, and then cooled to room temperature to obtain graphite oxide;

[0102] S2, graphite oxide and 2.2 kg of petroleum asphalt (softening point 250 ° C) were added to a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat-treated at 400 ° C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite was obtained;

[0103] S3, densifying the composite by pressing it in a hydraulic press at a pressure of 30 MPa, holding the pressure for 0.5 min, and reciprocating twice, and performing isostatic pressing densification treatment at a maximum isostatic pressing pressure of 70 MPa, holding the pressure for 3 min, and then crushing to obtain an intermediate product;

[0104] S4, carbonizing the intermediate product at 1250° C. for 16 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.

[0105] Example 5

[0106] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0107] S1, 20 kg of graphite raw material (D50 volume average particle size of 10 μm) was kept at a temperature of 550° C. and an oxygen content of 5% for 3 h, and then cooled to room temperature to obtain graphite oxide;

[0108] S2, graphite oxide and 2.2 kg of petroleum asphalt (softening point 250 ° C) were added to a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat-treated at 400 ° C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite was obtained;

[0109] S3, densifying the composite by pressing it in a hydraulic press at a pressure of 30 MPa, holding the pressure for 0.5 min, and reciprocating twice, and then performing isostatic pressing densification treatment at a maximum isostatic pressing pressure of 70 MPa, holding the pressure for 3 min, and then pulverizing to obtain an intermediate product;

[0110] S4, carbonizing the intermediate product at 1250° C. for 16 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this embodiment.

[0111] Example 6

[0112] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0113] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) was pressed in a hydraulic press at a pressure of 40 MPa, holding pressure for 0.5 min, and reciprocating three times. After pressing, it was crushed to an average particle size of 16 μm, and then isostatically pressed and densified at a maximum pressure of 80 MPa. After holding pressure for 3 min, it was crushed to obtain an intermediate product;

[0114] S2, the intermediate product and 2.2kg asphalt (softening point 250℃) were added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture was carbonized at 1250℃ for 16 hours under a nitrogen atmosphere. After carbonization, the mixture was dispersed, demagnetized and sieved to obtain the negative electrode material of this comparative example.

[0115] Example 7

[0116] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0117] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) was pressed in a hydraulic press at a pressure of 30 MPa, holding pressure for 0.5 min, and reciprocating three times. After pressing, it was crushed to an average particle size of 16 μm, and then isostatically pressed and densified at a maximum isostatic pressure of 100 MPa. After holding pressure for 3 min, it was crushed to obtain an intermediate product;

[0118] S2, the intermediate product and 2.2kg asphalt (softening point 250℃) were added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture was carbonized at 1250℃ for 18 hours under a nitrogen atmosphere. After carbonization, the mixture was dispersed, demagnetized and sieved to obtain the negative electrode material of this comparative example.

[0119] Comparative Example 1

[0120] The preparation method of the negative electrode material of this comparative example comprises the following steps:

[0121] 20 kg of graphite raw material (D50 volume average particle size is 16 μm) and 2.2 kg of asphalt (softening point 250°C) were added to a VC mixer and mixed for 25 minutes. After mixing, the materials were carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the materials were broken up, demagnetized and sieved to obtain the negative electrode material of this comparative example.

[0122] Comparative Example 2

[0123] The preparation method of the negative electrode material of this comparative example comprises the following steps:

[0124] 20 kg of graphite raw material (D50 volume average particle size is 10 μm) and 2.2 kg of asphalt (softening point 250°C) were added to a VC mixer and mixed for 25 minutes. After mixing, the materials were carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the materials were dispersed, demagnetized and sieved to obtain the negative electrode material of this comparative example.

[0125] Comparative Example 3

[0126] The preparation method of the negative electrode material of this comparative example comprises the following steps:

[0127] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) and 1.4 kg of petroleum asphalt (softening point of 120°C) were added to a VC mixer and mixed for 25 min. After uniform mixing, the mixture was heat-treated at 400°C for 4 h under a nitrogen atmosphere and cooled to room temperature to obtain a composite.

[0128] S2, densifying the composite by pressing it in a hydraulic press at a pressure of 20 MPa, holding the pressure for 0.5 min, and reciprocating twice, and then performing isostatic pressing densification treatment at a maximum isostatic pressing pressure of 50 MPa, holding the pressure for 3 min, and then crushing to obtain an intermediate product;

[0129] S3, carbonizing the intermediate product at 1250° C. for 14 h under a nitrogen atmosphere, breaking it up, demagnetizing it, and sieving it to obtain the negative electrode material of this comparative example.

[0130] Comparative Example 4

[0131] The preparation method of the negative electrode material of this embodiment includes the following steps:

[0132] S1, 20 kg of graphite raw material (D50 volume average particle size of 16 μm) was pressed in a hydraulic press at a pressure of 30 MPa, holding pressure for 0.5 min, and reciprocating three times. After pressing, it was crushed to an average particle size of 16 μm, and then isostatically pressed to a maximum pressure of 120 MPa. After holding pressure for 3 min, it was crushed to obtain an intermediate product;

[0133] S2, the intermediate product and 2.2kg asphalt (softening point 180℃) were added to a VC mixer and mixed for 25 minutes. After uniform mixing, the mixture was carbonized at 1250℃ for 14 hours under a nitrogen atmosphere. After carbonization, the mixture was dispersed, demagnetized and sieved to obtain the negative electrode material of this comparative example.

[0134] Test example

[0135] 1. Particle hardness (HIT) and elastic modulus (EIT) test

[0136] The particle hardness (HIT) and elastic modulus (EIT) tests of the negative electrode material were carried out using the Anton Paar NHT2 nanoindenter. The negative electrode material was placed on the sample stage of the indenter, and the static displacement mode was adopted. A glassy triangular pyramid indenter was used. The indenter contacted the sample and recorded at a set rate until the set indentation depth was 1200nm. After reaching the set depth, the load was maintained for 15s, and then the load was unloaded at the same rate, wherein the loading and decompression rate was 5mN / min and the Poisson's ratio was 0.3. The particle hardness was calculated based on the indentation depth and load size, and the elastic modulus was calculated based on the slope of the fitting line of the unloading curve from 40% to 98%. 10 particles were measured for each sample, and the average value was taken after the test.

[0137] 2. Tablet orientation test

[0138] The negative electrode material, carboxymethyl cellulose solution and styrene butadiene rubber solution are mixed in a mass ratio of 19.3:25:0.8, wherein the concentration of styrene butadiene rubber in the styrene butadiene rubber solution is 50wt%, and the concentration of carboxymethyl cellulose in the carboxymethyl cellulose solution is 1.2wt%. Use a high-speed disperser to disperse evenly to obtain a slurry; apply the slurry evenly on the surface of aluminum foil, and then place it in a constant temperature drying oven at a temperature of 80-95°C and bake for more than 6 hours until the slurry is completely dry to obtain a sample to be tested; grind the sample to be tested through 200 mesh, and use a tablet press to apply pressure of 0.5T (ton), 1T (ton) and 2T (ton) to the sample to be tested to obtain a sheet sample (tablet); place the tablet under a thickness gauge to obtain the initial thickness of the tablet after 10s, and then place the tablet in a constant temperature environment (25±3°C) for 16 hours, and use a thousand The thickness of the tablet after rebound (after standing for 16 hours) is measured with a ruler, and the tablet compaction density under the corresponding pressure is calculated based on the tablet mass, initial thickness and thickness after rebound; the tablet is analyzed using an X-ray diffractometer to obtain the crystal structure and orientation; the crystal plane orientation and the corresponding peak area are obtained by analyzing the X-ray diffraction pattern, and the OI value is calculated according to the tablet orientation OI value = I004 / I110, where I004 is the diffraction peak area of ​​the (004) crystal plane in the X-ray diffraction pattern, and I110 is the diffraction peak area of ​​the (110) crystal plane in the X-ray diffraction pattern. The test results can be seen Figure 2 and Table 1, in which x represents the tablet compaction density, y represents the tablet orientation OI value, Figure 2 In the table, X represents the tablet compaction density and Y represents the tablet orientation OI value.

[0139] 3. Particle size test

[0140] The Malvern 3000 laser particle size analyzer was used to test the D50 volume average particle size (D1) and the equal volume average particle size D2 of the negative electrode material. The sample, a small amount of dispersant (a mixture of ethanol, pure water and low-foaming surfactant) and pure water were added to a 50 mL beaker and stirred thoroughly with a glass rod to disperse the sample evenly. The sample was transferred to the sample cell of the Malvern 3000 laser particle size analyzer, and the equipment pump speed was set to 2400-2500 r / min and the frequency was 19.5 Hz for particle size testing.

[0141] 4. Sphericity Sh (90%) test

[0142] The sphericity of the negative electrode material was tested using a SYMPATEC QICPIC dynamic particle image analyzer. Sh(90%) refers to the ratio of the maximum diameter to the minimum diameter of 90% of the particles.

[0143] 5. Specific surface area SSA test

[0144] The specific surface area of ​​the negative electrode material was tested using a JW-DX dynamic surface area meter. Based on the theory of physical adsorption and the continuous flow method proposed by Nelsen and Eggertsen, the specific surface area of ​​the solid was determined. A gas mixture consisting of hydrogen as the carrier and nitrogen as the adsorbed gas was introduced into the sample tube. When the sample tube was immersed in liquid nitrogen and reached a low-temperature environment, the nitrogen in the mixture was physically adsorbed by the sample until saturation was achieved. At this point, the nitrogen ratio in the mixture changed. During the adsorption process, a high-precision thermal conductivity instrument performed the detection and calculation.

[0145] 6. Tap density test

[0146] The tap density of the negative electrode material was tested using the Quantachrome Dual Autotap device. 100 mL of the negative electrode material sample was placed in a measuring cylinder and mechanically vibrated 1000 times. The sample mass and volume after tapping were obtained and the tap density (g / cm 3 ) = sample mass / volume after tapping to calculate the tap density.

[0147] 7. Powder compaction density test

[0148] 1.0±0.05g of negative electrode material was introduced into the metal sleeve, and the sleeve loaded with the sample was placed in the center of the compaction density meter CARVER 4350.22. The pressure was slowly applied to 2T (tons), and the pressure was stopped. The second hand was started and the pressure was maintained for 30s. The pressure was quickly removed and the sample was taken out of the metal mold cavity and placed on the horizontal workbench of the thickness gauge. The height after compaction was measured with a thickness ruler. The powder compaction density (g / cm 3 ) = sample mass / volume after compaction to calculate the compacted density of the powder.

[0149] 8. First Coulombic efficiency test

[0150] The negative electrode materials of the embodiment and comparative example, carboxymethyl cellulose, and styrene-butadiene rubber were dissolved in pure water at a mass ratio of 96.5:1.5:2, respectively, with the solid content controlled to 50%, to obtain a negative electrode slurry. The negative electrode slurry was coated on a copper foil current collector, and after vacuum drying at 95°C, roller pressing, and pressurization, a negative electrode sheet was obtained. A metal lithium sheet was used as a counter electrode, and button batteries were assembled in an argon-filled glove box.

[0151] The button cell was charged and discharged at a current density of 0.1C in the charge and discharge range of 0.01 to 1.5V to obtain the first reversible specific capacity, first cycle charge capacity, and first cycle discharge capacity. The first coulombic efficiency was calculated according to the principle of first coulombic efficiency = first cycle discharge capacity / first cycle charge capacity.

[0152] 9. Cyclic stability test

[0153] Large single crystal lithium nickel cobalt manganese oxide (NCM523) was mixed with conductive carbon black and PVDF in a mass ratio of 94:3.0:3.0, and dissolved in N-methylpyrrolidone with a solid content of 50% to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil current collector, vacuum dried at 95°C, roller pressed, and pressurized to obtain a positive electrode sheet.

[0154] The negative electrode materials of the embodiment and comparative example, carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were dissolved in N-methylpyrrolidone at a mass ratio of 95:1.5:2.1:1.2, respectively, with a solid content of 50%, to obtain a negative electrode slurry; the negative electrode slurry was coated on a copper foil current collector, and the negative electrode sheet was obtained after vacuum drying at 95°C, roller pressing, and pressurizing.

[0155] The positive electrode sheet, separator and negative electrode sheet are assembled into a lithium-ion battery, and the electrolyte is injected to obtain a soft-pack battery of about 40mAh; wherein, the electrolyte is 1mol / L LiPF6 / ethylene carbonate (EC) + propylene carbonate (PC) + diethyl carbonate (DEC) + EMC (volume ratio 1:0.3:1:1), and the separator is a PP / PE / PP three-layer composite separator.

[0156] The above-mentioned soft-pack battery was used to test the cycling performance of the material. It was charged at a constant current of 1C to 4.20V, then charged at a constant voltage with the current gradually reduced to 0.05C. It was then discharged at a discharge rate of 1C to 2.75V. This charge-discharge cycle was repeated 400 times. The discharge capacity Q1 at the first cycle and the discharge capacity Q400 at the 400th cycle were measured. The 400-cycle capacity retention was calculated as 400-cycle capacity retention = Q400 / Q1 × 100%.

[0157] The test results are shown in Tables 1 and 2.

[0158] Table 1

[0159]

[0160]

[0161] Table 2

[0162]

[0163] In Table 2, D1 is the D50 volume average particle size of the negative electrode material, and D2 is the equal volume average particle size of the negative electrode material.

[0164] Figure 3 The SEM image of the negative electrode material in Example 1 shows that it has a certain sphericity. Figure 4It can be seen that the negative electrode materials of Examples 1 to 7 all meet the requirements of particle hardness of 0.28GPa to 0.4GPa, elastic modulus of 7.0GPa to 8.0GPa, and tablet orientation OI value of y, 4<y≤11, while the negative electrode materials of Comparative Example 1 do not meet the requirements of particle hardness of 0.28GPa to 0.4GPa, elastic modulus of 7.0GPa to 8.0GPa, and tablet orientation OI value of y, 4<y≤11; the negative electrode material of Comparative Example 2 does not meet the requirements of elastic modulus of 7.0GPa to 8.0GPa, the negative electrode material of Comparative Example 3 does not meet the requirements of particle hardness of 0.28GPa to 0.4GPa, and the negative electrode material of Comparative Example 4 has a compaction density of 1.61g / cm 3 When the range of the tableting orientation OI value is not met, Examples 1 to 7 have higher first coulombic efficiency, improved expansion performance, high 400-cycle capacity retention rate, and better overall electrical performance than Comparative Examples 1 to 4. It can be seen that the present invention can significantly improve the first coulombic efficiency and cycle stability by ensuring that the material meets the particle hardness of 0.28 GPa to 0.4 GPa, the elastic modulus of 7.0 GPa to 8.0 GPa, and the tableting orientation OI value of y, 4<y≤11.

[0165] Furthermore, compared with Examples 6 to 7, the negative electrode materials of Examples 1 to 5, while satisfying the particle hardness of 0.28 GPa to 0.4 GPa, the elastic modulus of 7.0 GPa to 8.0 GPa, and the tableting orientation OI value of y, 4<y≤11, further satisfy the following relationship: the tableting orientation OI value at different tableting densities is within the range of y1≤y≤y2, and y1=5.46x-3.78, y2=8.9x-7.76, the densification degree of the negative electrode material is further improved, and the structural stability is also further improved, so that the first coulombic efficiency of the negative electrode materials of Examples 1-5 is above 94%, the expansion performance is improved, and the 400-week capacity retention rate is ≥92.5%, which is better than Examples 6 to 7.

[0166] Furthermore, compared with Example 3, the negative electrode materials of Examples 1, 2, and 4 satisfy the following conditions: the particle hardness is 0.28 GPa to 0.4 GPa, the elastic modulus is 7.0 GPa to 8.0 GPa, the tableting orientation OI value is y, 4<y≤11, and the tableting orientation OI value at different tableting compaction densities is within the range of y1≤y≤y2, and y1=5.46x-3.78, y2=8.9x-7.76. The negative electrode materials of Examples 1, 2, and 4 further satisfy: the tableting orientation OI value is 5 to 9, the filling rate and structural stability of the negative electrode material are further improved, and the volume expansion of the material is further alleviated, so that the first coulombic efficiency of the negative electrode materials of Examples 1, 2, and 4 are all above 94.84%, and the 400-week capacity retention rate is ≥93.98%, which is better than Example 3.

[0167] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A negative electrode material, characterized in that The negative electrode material comprises natural graphite and amorphous carbon filled in the pores of the natural graphite; the particle hardness of the negative electrode material is 0.28GPa to 0.4GPa, and the elastic modulus is 7.0GPa to 8.0GPa; when the tablet compaction density of the negative electrode material is 1.5 to 2.0g / cm 3 When the negative electrode material is pressed, the OI value of the orientation is y, 4<y≤11.

2. The negative electrode material according to claim 1, characterized in that Includes at least one of the following features: (1) The particle hardness of the negative electrode material is 0.287 GPa, 0.288 GPa, 0.295 GPa, 0.308 GPa, 0.335 GPa, 0.356 GPa, 0.393 GPa, or any value within the range of any two of the above values; (2) The elastic modulus of the negative electrode material is 7.08 GPa, 7.15 GPa, 7.26 GPa, 7.45 GPa, 7.78 GPa, 7.9 GPa, 7.96 GPa, or any value within the range of any two of the above values; (3) When the compaction density of the negative electrode material is 1.5 to 2.0 g / cm 3 When the negative electrode material is oriented in the sheeting, the OI value of the negative electrode material is 4.05, 4.48, 4.68, 5.4, 5.53, 5.92, 6.1, 6.31, 6.58, 6.62, 7.38, 7.94, 8.11, 8.46, 8.51, 8.67, 9.73 or any value within the range of any two of the above values.

3. The negative electrode material according to claim 1, characterized in that Includes at least one of the following features: (1) The tablet orientation OI value y of the negative electrode material at different compaction densities satisfies the following conditions: y1≤y≤y2; wherein y1=5.46x-3.78, y2=8.9x-7.76, 1.5≤x≤2.0, and x is the value corresponding to the tablet compaction density of the negative electrode material; (2) When the compaction density of the negative electrode material is 1.5 to 2.0 g / cm 3 The negative electrode material has a pressed sheet orientation OI value y of 5 to 10.

4. The negative electrode material according to claim 1 or 2, characterized in that The negative electrode material satisfies at least one of the following characteristics: (1) The sphericity Sh (90%) of the negative electrode material is 0.90 to 0.95; (2) The D50 volume average particle size of the negative electrode material is 8 to 18 μm; (3) The average particle size of the negative electrode material is 10 to 20 μm.

5. The negative electrode material according to claim 4, characterized in that The shape coefficient φ of the negative electrode material and the sphericity Sh(90%) of the negative electrode material satisfy the following relationship: Δ=|φ-Sh(90%)|, and Δ≤0.08; wherein, φ=D1 / D2, D1 is the D50 volume average particle size of the negative electrode material, in μm; D2 is the equal volume average particle size of the negative electrode material, in μm.

6. The negative electrode material according to claim 1 or 2, characterized in that The specific surface area of ​​the negative electrode material is 2 to 5 m 2 / g.

7. The negative electrode material according to claim 1 or 2, characterized in that The tap density of the negative electrode material is 0.9 to 1.3 g / cm 3 .

8. The negative electrode material according to claim 1 or 2, characterized in that The powder compaction density of the negative electrode material is 1.7 to 2.0 g / cm 3 .

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The secondary battery includes the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Negative electrode active material for lithium ion secondary battery and lithium ion secondary battery

    CN104247107A

  • Graphite-based composite negative electrode material and preparation method and application thereof

    CN115347176A

  • Negative pole piece, battery and electric device

    CN118136780A

  • A negative electrode material, a negative electrode sheet, and a secondary battery

    CN119340376B

  • Carbon material for nonaqueous secondary battery, negative electrode, and nonaqueous secondary battery

    JP2014067644A